Folk music in Nigeria: a communion - Nzewi, Meki (International Library of African Music, 1980)
Folk music in Nigeria evolved as a corporate communal experience. It has been sustained as such, and continues to expand and enrich its resources as it crumbles ethnic barriers, incorporating broader geographical communities as it extends its ethnic identity. By this is postulated that folk music had narrow ethnic identities. Then through human tendencies of social interaction, direct borrowing and unconscious assimilation folk music began to identify larger ethnic unions in style and content. More recently, as a result of improved communication, education, other agencies of modern civilisation and neo-cultural aspirations, folk music areas in Nigeria are diffusing more and more into one another to form larger homogeneous blocks.
Keywords: Folk music; African Music; Nigeria